Baseline Assessments of Strength and Balance Performance and Bilateral Asymmetries in Collegiate Athletes. Issue 11 (November 2019) - Dai, Boyi; Layer, Jacob; Vertz, Cole; Hinshaw, Taylour; Cook, Ross; Li, Yongming; Sha, Zhanxin
Abstract : Abstract: Dai, B, Layer, J, Vertz, C, Hinshaw, T, Cook, R, Li, Y, and Sha, Z. Baseline assessments of strength and balance performance and bilateral asymmetries in collegiate athletes. J Strength Cond Res 33(11): 3015–3029, 2019—Injuries to upper and lower extremities comprise more than 70% of the total injuries in collegiate athletes. Establishing normative data of upper and lower extremity strength and balance may help guide postinjury rehabilitation and return-to-play decisions. The purposes of the current study were to develop the normative data of performance and bilateral asymmetries during 4 upper and lower extremity strength and balance tests in collegiate athletes and to quantify the correlations between strength and balance performance and bilateral asymmetries. A total of 304 male and 195 female Division I athletes from 14 sports performed a maximum push-up test to assess upper extremity strength, a countermovement jump test to assess lower extremity strength, an upper extremity reaching test to assess upper extremity balance, and a lower extremity reaching test to assess lower extremity balance. Bilateral ground reaction forces were collected for the push-up and jump tests. Reaching distances were measured for the 2 balance tests. Bilateral asymmetries were generally less than 10%. Significant sports effects were observed for all 5 performance variables ( p < 0.001) but not for asymmetry variables ( p ≥ 0.36). Weak correlations were found between strength and balance performance and asymmetries ( r < 0.3). Normative data are sex and sports specific in collegiate athletes. Increased asymmetries could be more individualized rather than sex and sports specific. When return-to-play decisions are made, athletes following injuries need to demonstrate less than 10% of asymmetries to be consistent with the normative data. Strength and balance should be evaluated and improved with specific focuses.